Financial Report Based on The Regional Financial Accounting System of The Regional Government of Bandung District - Surjono, Welly (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
The performance of organizations engaged in regional management areas has a regional financial accounting system in the form of activities ranging from recording to reporting business activities. The quality of government financial reporting is reflected in the results of the BPK audit. This literature review includes the basis for research and original research that will be the basis. The internal control system is a system formed to ensure the security of company assets. Internal control is a policy and an organized process and a process that integrates activities and operations to provide adequate assurance to achieve organizational goals. Research must be beneficial, and this research only has academic benefits. A quality local government financial accounting system and financial reports, as well as reference materials for further research on the same topic. Government financial reports may be of poor quality. This is related to the purpose of developing an accounting system which is none other than improving accounting management and internal control: increasing the level of financial reporting, increasing the reliability of accounting information, and providing accounting information.